ANALISIS PENGARUH PROFITABILITAS DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA - Ramadhan, Indra Dwi; Wicaksono, Dimas; -, Patriandari (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to analyze the effect of Profitability and Tax Planning on Earnings Management, a case study of Transportation Sector Companies for the 2019 - 2023 Period. The variables used are Profitability and Tax Planning as independent variables, and Earnings Management as the dependent variable. The research sample consisted of 10 transportation sector companies listed on the Indonesia Stock Exchange for the period 2019 - 2023. This sample was selected using purposive sampling method. The results of Logistic Regression testing show that Profitability has a regression coefficient value of 23.456 with a significance level of 0.023, meaning that it has a significant positive effect. Tax Planning has a regression coefficient value of -16.501 with a significance level of 0.999, which means that it has a negative and insignificant effect. The coefficient of determination (Nagelkerke R Square) of the regression model is 81.6%. While the remaining 18.4% is explained by other variables outside this research model.